The problem of granting citizenship to the sons of the terrorist ISIS - Ali Abdul Aziz Al-Jubouri (Journal of Madenat Alelem University College, 2023)
This study is one of the important studies that shed light on a sensitive issue experienced by Iraq and the region related to what the terrorist organization (ISIS) has done to control large areas of the land of Iraq. And the resulting crimes against women in particular, whether they were non-Muslims (Christians and Yazidis) or Muslims, as we studied the problem of granting nationality to the sons of the terrorist ISIS who were born on the land of Iraq to Iraqi parents, an Iraqi father, or an Iraqi mother, As well as addressing what happened to our people and our non-Muslim partners in the homeland, whether Christians or Yazidis and others, the true legal position on it. And the extent to which this can be achieved within the legal position based on the Iraqi constitution of 2005 and Nationality Law No. 26 of 2006, apart from the position on the crimes committed by members of this terrorist organization.